PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN KANTOR PUSAT PT. UNGGUL PRIMA (JAKARTA) - , Rosnelly Roesdy, Mery Ariani , Sri Indarti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of competence and work discipline on employee performance at the Head Office of PT. Superior Prima Jakarta. The research method used was quantitative with the primary data type in the form of a questionnaire with sampling using saturated sampling so that the number of samples in this study were 55 employees of the Head Office of PT. Superior Prima Jakarta. The results of this study indicate that competency influences employee performance. Work discipline variable influences employee performance. Competency and work discipline variables affect the performance of employees at the Head Office of PT. Unggul Prima Jakarta with influence of 51.5%. Keywords: Competence; Work Discipline, Employee Performance